PENGARUH PENGGUNAAN MEDIA INTERAKTIF DALAM MENINGKATKAN HASIL BELAJAR IPA DI SMP SWAKARYA TOLITOLI - Nasriani, Nasriani; Sitti Nuralan; Ikbal, Ikbal; Wihmat, Wihmat (Journal of Innovation Research and Knowledge, 2026)
This study aims to determine the effect of the use of interactive media on the learning outcomes of class VII students at SMP Swakarya Tolitoli, is a type of quantitative research with a pre-experimental type with a research design in the form of one-group pretest-posttest design. Respondents in this study were class VII students at SMP Swakarya Tolitoli. Data collection techniques used were observation sheets, student learning outcome tests and documentation. The data analysis technique used was descriptive statistical analysis and inferential statistical analysis for the test was the normality test and t-test. Based on the results of the research data analysis, the use of interactive media has an effect on student learning outcomes. Learning outcomes are proven from the results of the hypothesis test that the Sig. value is 0.002 <0.05 which states that H1 is accepted so that interactive media has an effect on student learning outcomes.